PHILOSOPHY OF GOD IN THE PERSPECTIVE OF BEDIUZZAMAN SAID NURSI - Zaprulkhan, Zaprulkhan (KALAM, 2018)
Discourse about the existence of God, in the realm of philosophy, included in the circle category metaphysics or also called the first philosophy. In the circle of non-Muslim philosophers, the discourse of the existence of God is elaborated by Thomas Aquinas by presenting five arguments, called cosmological propositions. As for the classical Muslim, scholar Ibn Sina appears to describe the existence of God through the argument of al-jawas or contingency which divides the form into three categories: the necessary existence (wajib al-wujud), the possible form (Mumkin al-wujud) and the impossible being (mumtani ' al-wujud). In the modern context of the twentieth century, Said Nursi elaborated philosophy of the divinity more broadly using cosmological, ontological, teleological, and intuitive arguments. Said Nursi describes all these arguments philosophically by using various illustrations. This article will discuss the philosophy of God in the perspective of Bediuzzaman Said Nursi.